Business Model Canvas Berbasis Ekonomi Sirkular untuk Produk Ikan Keumamah Kemasan di Gampong Deah Raya Kota Banda Aceh - Nur Izzaty; Kana Puspita; Faradilla Fadlia; Marzuki Ansari (Universitas Teuku Umar, 2026)
This community service program aims to provide education and assistance to the keumamah producers in Deah Raya Village, City of Banda Aceh, to develop a sustainable business model that integrates circular economy principles using the approach of Business Model Canvas (BMC). The activities commenced with a preliminary survey involving observations and interviews, followed by educational sessions and focus group discussions (FGDs). The next stage consisted of workshops on preparing a business model using the BMC framework, and the final activity was output socialization and dissemination. The results of the program produced a visual BMC canvas consisting of nine building blocks that had integrated circular economy principles. These were reflected, among others, in the inclusion of compost fertilizer as a by-product derived from production waste processing, which added value to environmentally friendly keumamah products; agropreneurs as one of the market segments; and an additional revenue stream from compost fertilizer sales. The business model is expected to help the business actors of keumamah fish in Deah Raya Village operate their business sustainably, increase the economic value of their products, and reduce negative environmental impacts.